İsmail Bozkurt’un “Bir Gün Belki” İsimli Romanında Kıbrıs Türk Folkloruna Dair Tespitler / Findings on the Cypriot Turkish Folklore in the Novel of Ismail Bozkurt Named “Maybe One Day...” - Yeniasır, Mustafa; Gökbulut, Burak (Journal of History Culture and Art Research, 2017)
Abstract Literature is a social institution because it uses the language which uses the language as means, and also because the literature gets feed from the miscellaneous events happened throughout history. It is possible to see social contents in several poets and authors who throw light to the society. In these works, the artists give place to the traditions, customs and life styles of the society they live in. İsmail Bozkurt is known specially for the work of art he wrote in the field of novel in Cyprus Turkish Literature; in the novels, he tells the stories about national struggle of Cypriot Turks, he also gives place to social and cultural life of the society, he presents the Cyprus dialect in necessary fields. In one of the most significant novels of his; “Maybe One Day...’’ which is also translated in Azerbaijani Turkish and in Russian, Ismail Bozkurt tells a story about the existence struggle of Cypriot Turks in 1960’s where is also a love story of two young people. The author provides successful descriptions in this 358-paged novel; both the events presented and the places where these events happen in draw the picture of those days. Nonetheless, this novel named “Maybe One Day...’’ which is published in 2002, has a feature of being a historical novel with all the components presented regards to Cypriot Turkish Folklore at its time. Öz Edebiyat, hem sosyal bir araç olan dili kullandığı hem de toplumların tarih boyunca yaşamış olduğu çeşitli olaylardan beslendiği için sosyal bir kurumdur. Yaşadığı topluma ışık tutan birçok şair ve yazarda, sosyal içerikli eserler görmek mümkündür. Söz konusu eserlerde sanatçılar, içinde yaşadıkları toplumun geleneklerine, göreneklerine ve yaşam tarzlarına yer vermişlerdir. Kıbrıs Türk Edebiyatında özellikle roman sahasında yazmış olduğu eserlerle tanınan İsmail Bozkurt, Kıbrıs Türkünün millî mücadelesini anlattığı yapıtlarında içinde bulunduğu toplumun sosyal ve kültürel yaşamına da geniş yer vermiş, gerekli görülen yerlerde de abartıya düşmeden Kıbrıs ağzını başarıyla yansıtmıştır. İsmail Bozkurt, en önemli romanlarından biri olan ve hem Azerbaycan Türkçesine aktarılan hem de Rusçaya çevrilen “Bir Gün Belki” isimli eserinde iki gencin yaşadığı aşk ekseninde Kıbrıs Türkü’nün 1960’lı yıllarda vermiş olduğu varoluş mücadelesini anlatmıştır. Yazar, 358 sayfalık bu hacimli romanında başarılı tasvirleriyle dikkat çekmiş; gerek ele aldığı olaylarla gerekse bu olayların geçtiği mekânlarla âdeta o yılların resmini çizmiştir. Bununla beraber, 2002 yılında yayınlamış olduğu “Bir Gün Belki” isimli romanında dönemin tarihi özellikleriyle birlikte Kıbrıs Türk Folkloruna dair birçok unsura yer vererek eserine tarihi roman özelliği kazandırmıştır.